Electricity 3 : power generation and delivery - Keljik, Jeff, author (Clifton Park, NY : Thomson Delmar Learning, 2006)
Electricity 3 explores various types of generators and the delivery of single phase and 3-phase power to the customer site. The Eighth Edition is updated to the 2005 National Electrical Code and includes safety features from the power supply industry and current OSHA standards where applicable. New concepts in generation for standby or emergency power have been added, while traditional methods have been organized to provide understanding and transition to the modern methods. This book gives concise, useful information on the connections, the concepts of generation, and control for the production of electricity.
Includes index
In English text.
Keywords: Electric machinery -- Direct current; Electric controllers; Electric transformers